The Influence of Authoritarian Political Configuration in The Presidential Government System on Constitutional Court Decisions - Salamony, Jetter Wilson; Santiago, Faisal (Greenation Publisher & Yayasan Global Resarch National, 2025)
The authority of the Constitutional Court, which should ideally result in independent decisions free from external influence, has proven to be very difficult to achieve. This is because the decisions of the Constitutional Court are also influenced by political interests. This situation places society, as seekers of justice, in a challenging position when dealing with disputes in the Constitutional Court, as it is not easy to confront the political interests of those in power. The legitimacy of political power formed through group dynamics creates an authoritarian political configuration, which not only impacts the democratic life of a nation but also undermines the enforcement of law. In terms of state governance, Indonesia explicitly acknowledges a democratic political configuration as enshrined in its Constitution, which firmly recognizes Indonesia as a democracy based on Pancasila. Changes in the practice of democratic politics have significantly affected various legal aspects in Indonesia, including legal politics, legal products, and even the decisions of the Constitutional Court (MK), which holds the authority to adjudicate and decide cases related to judicial review. Ultimately, the Constitutional Court has also become part of state institutions affected by the shift from democratic political practices to authoritarian political configurations. This research is conducted normatively using primary data derived from Constitutional Court Decisions Number 90/PUU-XXI/2023, 60/PUU-XXII/2024, and 70/PUU-XXII/2024, focusing on the outcomes of decisions influenced by political interest tendencies. The research data is also supplemented by other sources obtained through legal literature and information from various media. The results of the research conducted found that: The position of the Constitutional Court as a state institution within a presidential system is not one that operates independently, despite being part of the judiciary. The system of separation of powers allows for the Constitutional Court to be influenced by both executive and legislative powers. In an authoritarian political configuration, the creation of large coalitions in the legislative and executive branches automatically leads to dominance that directly affects the decisions of the Constitutional Court. This is due to the composition of judges on the Constitutional Court, which consists of three judges nominated by the President, three by the DPR (House of Representatives), and three by the Supreme Court.